Kemampuan Berpikir Kritis Matematis Ditinjau dari Motivasi Belajar Pada Model Game Based Learning Berbantuan Quizlet - Adiba, Farah; Kartono, Kartono (Papanda, 2026)
Critical thinking skills are one of the 21st century skills that students need to master. However, the results of the Programme for International Student Assessment (PISA) show that the mathematical critical thinking skills of students in Indonesia are still relatively low. One effort to improve these skills is through the selection of appropriate learning models and media. This study aims to: (1) examine the quality of the implementation of the Quizlet-assisted Game-Based Learning model on the mathematical critical thinking skills of Year 7 students and (2) analyse the effect of learning motivation on students' mathematical critical thinking skills. This study used a quantitative experiment with a sample of seventh grade D students as the experimental group and seventh grade E students as the control group. Data were collected through tests, questionnaires, observations, and validation, then analysed quantitatively. The results showed that Quizlet-assisted Game-Based Learning was effective in improving mathematical critical thinking skills. Learning motivation had a 33.2% effect on students' mathematical critical thinking skills. Therefore, the Quizlet-assisted Game Based Learning model is recommended as an alternative method of mathematics learning to improve students' mathematical critical thinking skills and learning motivation. Further research is recommended to examine the application of this model in different subjects or levels of education and to add other variables in order to obtain more comprehensive results.